Pengaruh Penggunaan Tris Dalam Pengencer Susu Skim Terhadap Resistensi Spermatozoa Sapi Simmental Pasca Pembekuan - Hoesni, Fachroerrozi (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2016)
This study aimed to determine the effect of the use of tris in skim milk diluent in immune Simmental cattle spermatozoa after freezing. Randomized block design with 5 treatments and 6 blocks of ejaculation was applied. The treatments were P0 = 93% skim milk diluent without tris + + 7% glycerol, P1 = 83% skim milk diluent tris + 10% + 7% glycerol, P2 = 73% skim milk diluent tris + 20% + 7% glycerol, P3 = skim milk diluent tris 63% + 30% + 7% glycerol, P4 = skim milk diluent trsi 53% + 40% + 7% glycerol. The results showed that the use of skim milk diluent tris in the P2 treatment exert a highly significant (P <0.01) in maintaining the survival of spermatozoa after freezing Simmental cattle. The results of this study concluded that the use of tris in skim milk dilution to the extent of 20% to maintain the vitality of spermatozoa after freezing Simmental cattle.